Synthesis, structural and optical characterization of CuO, CeO₂ and (CuO)ₓ(CeO₂)₁-ₓ nanoparticles via thermal treatment method - Baqer, Anwar Ali (2017)
Metal oxide semiconductor nanocrystals are regarded as one of the most important inorganic nanomaterials because of their electronic, optical, electrical and magnetic, properties. These properties are dependent on the chemical composition and microstructural characteristics in which the particle size and shape might be controlled in the fabrication processes. Amongst all metal oxide nanoparticles (NPs), copper oxide (CuO), cerium oxide (CeO2) and (CuO)x(CeO2)1-x NPs have intriguing properties for the development of novel electronic devices, solar cell, sensor, catalyst and medical applications due to their excellent optical and electronic properties. Therefore, further study is needed to synthesize by other methods and characterize these properties. CuO, CeO2 and binary (CuO)x(CeO2)1-x NPs were successfully synthesized by thermal treatment method.The XRD diffraction patterns reveal monoclinic structure for CuO NPs and cubic fluorite structure for CeO2 NPs. With no other impurities can be detected, indicating the high purity of the final products. The crystallite size was found to increase from 12.64-25.76, 8.71-22.74 and 5.12-15.34 nm for CuO and 6.45-22.18, 7.25-18.76 and 6.15-11.43 nm for CeO2 with evolution in calcination temperatures 500-800 οC at a concentration of PVP 0.03, 0.04 and 0.05 g/ml respectively. These results were in agreement with the transition electron microscopy results which showed the formation of CuO and CeO2 in nanoscale size. The average particle size estimated by TEM was found to increase from15.53 to 30.00 nm, 9.75 to 23.54 nm and 4.25 to 16.93 nm for CuO and 5.15 to 24.19 nm, 4.32 to 20.24 nm and 3.00 to 10.62 nm for CeO2 with increase in calcination temperature 500-800 οC at a concentration of PVP 0.03, 0.04 and 0.05 g/ml respectively. The FTIR results confirmed the removal of polymer and the presence of metal oxides nanoparticles at calcination temperatures 500-800 oC. The elemental composition of the samples obtained by EDX spectroscopy has further evidenced the formation highly pure CuO and CeO2 NPs. Furthermore, the optical band gap of the samples was calculated using Kubelka-Munk function for calcination temperatures 500-800 oC. The band gap was found to decrease from 2.56 to 2.34 eV, 2.75 to 2.42 eV and 2.78 to 2.46 eV for CuO and 3.37 to 3.31eV, 3.38 to 3.32 eV and 3.45 to 3.41 eV for CeO2 at a concentration of PVP 0.03, 0.04 and 0.05 g/ml respectively. A reduction in the energy band gap with increasing calcination temperatures is attributed to the increase in the particle size. The PL spectra at calcination temperatures 500-800 oC showed that the increment in the intensity with increasing calcination temperatures is attributed to the expansion in the particle size. Due to the control over particle sizes of CuO and CeO2 that this technique allows by the varying of PVP concentration and calcination temperature, semiconductor materials with wide band gaps can be produced. These materials are able to absorb UV–visible wavelengths of solar energy, making them suitable for use within solar cell applications. Furthermore, CeO2 materials produced by this method may be acceptable for use in manufacturing UV filters, catalysts and photoelectric devices. From the XRD diffraction patterns results, the prepared (CuO)x(CeO2)1-x NPs at different calcination temperatures range from 500-800 οC showed that the crystallite size was increased in the range of 11.25-34.17 nm for (CuO)0.6(CeO2)0.4 with monoclinic and cubic fluorite structures together with no other impurities can be detected, indicating the high purity of the final products. These results were in agreement with the transition electron microscopy results which showed the formation of (CuO)x(CeO2)1-x in nanoscale size. The average particle size determined by TEM was found to increase 11.96-31.83 nm for (CuO)0.8(CeO2)0.2 and 2.97-10.70 nm for (CuO)0.2(CeO2)0.8 with increase in calcination temperature 500-800 οC respectively. At the lower concentration of CuO and with calcination temperature, the particle size smaller and consistent for binary (CuO)x(CeO2)1-x. The FTIR results confirmed the removal of polymer and the presence of metal oxide nanoparticles at calcination temperatures 500-800 oC. The elemental composition of the samples obtained by EDX spectroscopy has further evidenced the formation of (CuO)x(CeO2)1-x nanoparticles. In addition, the optical band gap of the samples was calculated using Kubelka-Munk function for calcination temperatures 500-800 oC. The band gap was found to decrease from in the range of 2.82, 3.22 to 2.72, 3.13 eV for (CuO)0.8(CeO2)0.2 and 2.90, 3.30 to 2.83, 3.24 eV for (CuO)0.2(CeO2)0.8. A decrease in the energy band gap with increasing calcination temperatures is attributed to the increase in the particle size. The PL spectra at calcination temperatures 500-800 oC showed that the increment in the intensity with increasing calcination temperatures is attributed to the increase in the particle size. Due to the control over (CuO)x(CeO2)1-x particle sizes that this technique allows by the varying of PVP concentration and calcination temperature, semiconductor materials with multiple band gaps can be produced. These materials are able to absorb specific wavelengths of solar energy, making them very suitable for use within solar cell and sensor applications.